2015
DOI: 10.14687/ijhs.v12i1.3196
|View full text |Cite
|
Sign up to set email alerts
|

The objectives of disaster education from teachers’ perspectives

Abstract: This study aims to examine teachers' judgments on the objectives of disaster education regarding basic three aspects; clarity, measurability and attainability. A 3-point Likert-type scale was developed, and completed by 142 teachers who participated in several in-service trainings about disaster education. Descriptive statistics were carried out to analyze the data. Results of this study revealed that there was no single objective that teachers perceived as clear, measurable and attainable at one hundred perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…(Toya and Skidmore, 2007;Omelicheva, 2011;D Selby and Kagawa, 2012) supported a stronger resilience by adopting the strategy of investing today and saving lives tomorrow. Few authors demonstrated that the best actions are people-centered and that pre-disaster investments are essential as the first step in reducing chronic vulnerability to disasters (Karnawati et al, 2015;Khorram-Manesh et al, 2015;Erdur-Baker, 2015). Some studies (Komac et al, 2013;Takahashi et al, 2015) emphasized on building and maintaining relationships between and within communities, between governments and organizations, across departments, and so on to enhance the accessibility of resources, services, and information under an integrated disaster management system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…(Toya and Skidmore, 2007;Omelicheva, 2011;D Selby and Kagawa, 2012) supported a stronger resilience by adopting the strategy of investing today and saving lives tomorrow. Few authors demonstrated that the best actions are people-centered and that pre-disaster investments are essential as the first step in reducing chronic vulnerability to disasters (Karnawati et al, 2015;Khorram-Manesh et al, 2015;Erdur-Baker, 2015). Some studies (Komac et al, 2013;Takahashi et al, 2015) emphasized on building and maintaining relationships between and within communities, between governments and organizations, across departments, and so on to enhance the accessibility of resources, services, and information under an integrated disaster management system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Komac et al, 2013;Sauerborn and Ebi, 2012;United Nations, 2019) substantiated the claim that long-run disaster reduction policies require efforts to improve the disaster education for a foolproof DRR. Field-workers (D Selby and Kagawa, 2012;Khorram-Manesh et al, 2015;Erdur-Baker, 2015) suggested for imparting systematized training to schools and communities based on the lessons drawn from past disasters. Investigators (Neal, 2005;Neumayer and Plümper, 2007;Komac et al, 2013;Bui et al, 2014) concluded that a meaningful and essential disaster science education in schools and colleges fosters an attitude of stronger resilience in people.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations